Fatherland - Harris, Robert 1957- (2007)
It's 1964 in Hitler's Germania. Since Hitler's forces won World War II, the world has believed the Reich's claim that six million Jews were resettled "in the East." Now a German policeman and an American journalist have uncovered the truth about the Nazi death camps. Hitler's reign will be destroyed if the world finds out, which is something the Gestapo can never allow.
Orig.: USA 1994
Keywords: Feature films; Television adaptations; Television plays